Scaffold' : A Protocol for Developing Curriculum-Led Human-Centred Next Generation Learning Environments in Higher Education : Final Report. - Sherringham, Susan; Clark-Coolee, Bronwyn; Buchanen, Kylie; Bawa, Mukti; Stewart, Susan; Serle, Susan; Kelly, Michelle; McKenzie, Jo; Byrne, Alex; Lowe, David; McWhinnie, Louise (Australian Learning and Teaching Council (ALTC), 2014)
Final report from a project that built on institutional strategies, research, and learning space initiatives and was developed using collegial institutional teams, through case studies at UTS and elsewhere, and through cross institutional workshops and prototyping. The project used: 1. case studies of existing curriculum-led learning spaces, focusing on design processes, redesign of curricula, integrated technology, and their relationship to spatial design and students' experiences of learning in these spaces, 2. a framework of protocols, tools and models for the design of new curriculum-led, human-centred learning spaces, formal & informal, and 3. workshops for stakeholders and others, from UTS and other institutions, to evaluate and refine the initial framework. In the project's second year, evaluation and dissemination of the framework was through workshops with other institutions.